Values-Led Management: The Guidance of Place-Based Values in Environmental Relationships of the Past, Present, and Future - Artelle, Kyle A.; Stephenson, Janet; Bragg, Corey; Housty, Jessie A.; Housty, William G.; Kawharu, Merata; Turner, Nancy J. (2018)
The prevalence of widespread, human-caused ecological degradation suggests that fundamental change is needed in how societies interact with the environment. In this paper we argue that durable models of environmental relationships already exist in approaches of place-based peoples, whose values connect people to their environments, provide guidance on appropriate behaviors, and structure sustained people-place relationships. To illustrate, we identify and discuss concordant values of indigenous peoples at opposite ends of the Pacific Ocean: the Māori of Aotearoa (New Zealand), and First Nations of the West Coast of Canada. We find that values of relatedness to, respect of, and reciprocity with other species and places correspond with sustained long-term relationships between people and places, and illustrate with examples from both regions. We propose that by integrating a values-led foundation into management broadly, values-led management could enable similar sustained relationships in places where they have been recently disrupted or where they are altogether lacking. We characterize values-led management as being founded on values that underpin stewardship-like relationships between people and place and that in turn guide related objectives, policies, and practices. We examine two contemporary values-led management plans that follow this structure, and provide additional examples of emergent values-led approaches elsewhere. From these we compile a set of questions that might guide the conception of place-based values-led management in decolonizing contexts, in contexts where people have a desire for place-based approaches but have not yet distilled foundational values for guidance, or in contexts where people have a united set of values but have not yet translated them into specific management approaches. We conclude by discussing both the challenges and learning opportunities that the resumption, or commencement, of values-led management might entail.